HUBUNGAN MEKANISME KOPING DAN DUKUNGAN SOSIAL DENGAN STRESS AKADEMIK SAAT PANDEMI COVID-19 DI SMK MULIA KARYA HUSADA - Della Yunita (2022)
Online learning is one of the learning solutions during the COVID-19 pandemic so that it can have a psychological impact on teenagers. Learning that is done online at home, of course, requires a support system that can come from family, peers or meaningful people so that teenagers can feel more cared for. In addition to social support, coping mechanisms are no less important in conducting the online learning process. This study aims to determine the relationship between coping mechanisms and social support with adolescent academic stress in the learning process during the COVID-19 pandemic in students at SMK Mulia Karya Husada. The research design was cross sectional with a stratified random sampling technique of 116 students. The study was to used ESSA, MSPSS, and Brief cope questionnaire. Analysis using chi square. The results of the analysis between coping mechanisms obtained p value = 0.004 (<0.05) meaning that there is a relationship between coping mechanisms and adolescent academic stress. While the results of the analysis on social support with academic stress obtained p value = 0.002 (<0.05), meaning that there is a relationship between social support and adolescent academic stress. therefore, it is hoped that teachers can provide education about the importance of social support and coping mechanisms in conducting learning during the COVID-19 Pandemic so as to reduce academic stress felt by students.